The Impact of Augmented Reality (Assemblr Edu) on Descriptive Writing in an Indonesian EFL Curriculum: A Quasi-Experimental Study - Nadilla Tiandi Maharani; Monalisa Monalisa; Iin Nirwana (Yayasan Sembilan Pemuda Indonesia, 2026)
This study investigated the instructional impact of Augmented Reality (AR) integration through Assemblr Edu on junior high school students’ descriptive writing within the competency framework of Kurikulum Merdeka Phase D. A quasi-experimental design involving 56 seventh-grade students was implemented using a non-equivalent control group structure. Students’ writing performance was measured through analytic scoring of pre- and post-tests, and the data were analyzed using non-parametric statistics due to non-normal distribution. The Wilcoxon Signed-Rank Test indicated significant improvement within the AR-supported group with a large practical effect. Furthermore, the Mann–Whitney U test was conducted to compare post-test scores between groups, showing that although the difference was statistically meaningful, the conventionally taught group demonstrated a larger raw score gain, which should be interpreted in relation to baseline differences between groups. The contribution of this study lies in positioning AR not merely as a technological intervention but as a pedagogically mediated instructional tool. While earlier studies frequently emphasize motivational benefits, this research combines performance-based assessment with instructional design considerations. The findings suggest that AR supports idea generation and descriptive elaboration through visual scaffolding, yet its effectiveness depends on structured guidance, duration of exposure, and teacher facilitation. Overall, the results indicate that the influence of educational technology on writing development emerges primarily from pedagogical orchestration that structures the use of digital affordances within instructional practice.